ANALISIS METODE BURHANI, BAYANI, DAN IRFANI DALAM PERNIKAHAN DINI YANG TIDAK TERCATAT DI PENGADILAN - Winarni Winarni; Ghazali; Tuti Harwati (Islamic Family Law, STAI Sangatta Kutai Timur, 2025)
Indonesian marriage law ideally stipulates that marriage should be entered into by men aged 21 and women aged 19, reflecting the assumption that individuals at this stage have reached sufficient maturity to assume marital responsibilities and roles. However, in practice, marriages involving minors—many of whom are still in school—remain prevalent. Early marriage has increasingly become a normalized phenomenon within society and has even emerged as a trend among younger generations. This study employs field research with an empirical approach to examine the factors influencing early marriage and its impacts. Primary data were obtained through direct interviews with individuals who entered into early marriage, while secondary data were collected from academic articles and relevant literature, including analyses based on the burhani, irfani, and bayani methodological perspectives. The findings identify several key factors contributing to early marriage, including economic pressure, low educational attainment, family and parental influence, individual motivation, exposure to technology and social media, as well as customary and cultural norms. The study further reveals that early marriage generates significant negative impacts, particularly on adolescents and children. Married adolescents, especially those who become pregnant at a young age, face heightened health risks such as anemia, which contribute to increased maternal and infant mortality rates. Early marriage also limits access to education, restricts employment opportunities, accelerates the loss of adolescence, and ultimately contributes to higher unemployment rates. Children born from early marriages are more likely to experience low birth weight, premature birth, and increased health vulnerabilities. Based on the perspectives of the interviewed participants, early marriage is considered better avoided due to its extensive negative consequences, despite the presence of limited perceived benefits.